"No man is an island": Effects of interpersonal proximity on spatial attention. Issue 1 (1st October 2016) - Szpak, Ancrêt; Nicholls, Michael E.R.; Thomas, Nicole A.; Laham, Simon M.; Loetscher, Tobias
Abstract : While it is generally acknowledged that another person's presence can influence how we behave within our environment, our understanding of the mechanisms underlying this influence is limited. Three experiments investigated the effect of social presence on the lateral distribution of spatial attention. Shifts in spatial attention were measured using line bisection, while participants sat in each other's personal space. An attentional withdrawal was observed, whereby attention moved away from the other person when the same task was using turn-taking (Experiment 1) and independent responding (Experiment 2) paradigms. When participant pairs engaged in different tasks (Experiment 3), attentional withdrawal was no longer observed. Our results strongly suggest that the influence of interpersonal proximity on attention merits greater consideration than it has received from researchers investigating social effects on cognition.